2020
DOI: 10.1002/bjs5.50337
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-intensity exercise training on physical fitness, quality of life and treatment outcomes after oesophagectomy for cancer of the gastro-oesophageal junction: PRESET pilot study

Abstract: Background: Treatment for cancer of the gastro-oesophageal junction (GOJ) can result in considerable and persistent impairment of physical fitness and health-related quality of life (HRQoL). This controlled follow-up study investigated the feasibility and safety of postoperative exercise training. Methods: Patients with stage I-III GOJ cancer were allocated to 12 weeks of postoperative concurrent aerobic and resistance training (exercise group) or usual care (control group). Changes in cardiorespiratory fitnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
0
9
0
2
Order By: Relevance
“…[35][36][37][38] Impairments of physical fitness and HRQoL already present before surgery can be further exacerbated by the surgical procedure, adjuvant chemotherapy and persistent malnutrition. 39 It has been observed that impairments of cardiorespiratory fitness persist for up to 2 years after surgical treatment, 40 muscle mass may continue to decline for up to 1 year after treatment, 41 and HRQoL can remain impaired for years. 42 While this again provides a strong rationale for post-surgery rehabilitation the (promising) evidence in this area is so far limited.…”
Section: Rehabilitation For Other Groups Of Patients Undergoing Oncol...mentioning
confidence: 99%
See 1 more Smart Citation
“…[35][36][37][38] Impairments of physical fitness and HRQoL already present before surgery can be further exacerbated by the surgical procedure, adjuvant chemotherapy and persistent malnutrition. 39 It has been observed that impairments of cardiorespiratory fitness persist for up to 2 years after surgical treatment, 40 muscle mass may continue to decline for up to 1 year after treatment, 41 and HRQoL can remain impaired for years. 42 While this again provides a strong rationale for post-surgery rehabilitation the (promising) evidence in this area is so far limited.…”
Section: Rehabilitation For Other Groups Of Patients Undergoing Oncol...mentioning
confidence: 99%
“…In addition to several small observational studies which make it difficult to separate the effects of the rehabilitative interventions from the natural course of recovery after surgery, there are three recent randomized controlled trials available which indicate feasibility, safety and efficacy of (high intensity) exercise training in the postoperative phase in these patients. 39,43,44…”
Section: Rehabilitation For Other Groups Of Patients Undergoing Oncol...mentioning
confidence: 99%
“…2,[46][47][48][49][50][51][52][53] For the studies assessing periand postoperative physiotherapy, there were six RCTs [54][55][56][57][58][59] comparing an intervention with a control group, and one study 60 compared two different types of physiotherapy. Among the cohort studies, eight studies [61][62][63][64][65][66][67][68] S5. Finally, six RCTs 38,[40][41][42][43][44] and eight cohort studies 2,46-49,51-53 assessing prehabilitation, and five RCTs [54][55][56]58,59 and five cohort studies 61,62,65,67,68 S6 for each analysis.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…In patients with gastrointestinal cancer, several studies suggest that exercise before or shortly after surgery is safe and feasible [11][12][13][14][15][16] and that perioperative exercise shortens the length of postoperative hospitalization [17], reduces the incidence of postoperative complications [18], restores immune function following surgery [19], lowers the risk of treatment failure [16], and improves chemotherapy completion rates [20] and response [21]. These findings provide an intriguing rationale for applying exercise as a supportive perioperative care strategy in patients with gastrointestinal cancer, with potential implications for treatment outcomes.…”
Section: Exercise Training In Surgical Oncologymentioning
confidence: 99%